Rational technologies of filling masses formation at undergrounds mines of JSC «KAZZINC» - Y N Shaposhnik; S N Shaposhnik (RUDN Journal of Engineering Research, 2009)
Issues on improvement of rheological properties of backfilling mixtures owing to the use of plastifying agents as additives to the mixtures composition were studied in the work, and rational schemes were developed for mining waste supply to the empty exploited rooms not raising it to the surface.